A report on the practice in industry in fish culture - Jacang, Alfredo C. (Miagao, Iloilo College of Fisheries, University of the Philippines, 1950)
The work mentioned in this report includes actual and practical application of fishpond management. It involves research activities possible, which are mainly fishpond fertilization, mono- and polyyoulty of carps, hito culture, tilapia culture, rice and fish farming and development of supplementary feeds for nutritional requirement of fish.jaca
Keywords: Fish-culture.